MOLECULAR AND LATTICE DYNAMICS STUDY OF THE MGO-SIO2 SYSTEM USING A TRANSFERABLE INTERATOMIC POTENTIAL - Belonoshko A.B.; Dubrovinsky L.S. (My University, 1996)
We have developed a transferable interatomic potential to describe interatomic interaction in minerals of MgO-SiO2 composition. The potential was obtained in such a way that except for the data on thermoelastic properties of MgO (periclase) and SiO2 (α-quartz) at ambient conditions, no experimental information on minerals of intermediate chemical composition was used. This potential was used to derive thermoelastic properties of minerals of that composition and melting of periclase and MgSiO3-perovskite. Calculated and experimental properties are in reasonable agreement wherever comparison is possible. The calculated melting curves in this study are in good agreement with the melting curves calculated earlier utilizing other models of interatomic potentials (Belonoshko, 1994a,b;Belonoshko and Dubrovinsky, 1995, 1996a). Equations of state of periclase, MgSiO3-perovskite, and the melts of MgO, MgSiO3, and Mg2SiO4 compositions are provided. These equations and melting curves obtained by two-phase molecular dynamic simulations were used to calculate the change of volume, entropy, and enthalpy at the melting pressure and temperature. This was used to calculate the MgO-MgSiO3 eutectic diagram at the pressure of the core-mantle boundary. The calculation reveals that the eutectic melting temperature is 5000 K, which is almost equal to the temperature of the liquid iron adiabat at the outer core side of core-mantle boundary. It provides conditions of melting, the composition of melt (close to olivine), and an equation of state of thermal plumes generated at the core-mantle boundary.